PENGARUH BEBAN KENDARAAN TERHADAP KERUSAKAN JALAN - Melkius daby; Nicky Rampengan; Toar Pangkey (Sustainable Construction (SUSCON), 2024)
The Kimbim-Pyramid Road in Jayawijaya district is the main road or connecting road from Jayawijaya district to four districts, each of which consists of Lanny Jaya district, Tolikara district, Puncak Jaya district and Puncak Papua district. Of the four districts mentioned above, these are districts that have been expanded by Jayawijaya district since 2007. The writer used as research material the Kimbim-Pyramid road in Jayawijaya district. The connecting road that will be used as research material is approximately 4 km out of a total length of 40 km starting from STA 1 to STA 4+0. This type of research involves analyzing literature to find theories that are relevant to the problem being investigated. The data collection method in this research uses secondary data and primary data. The research results show; 1) Average daily traffic data found 8,251 light vehicles and 2,813 heavy vehicles. This results in a percentage of light vehicles of 76.47% and heavy vehicles of 23.53%. 2) The damage is located on the wheel tracks, indicating that the road is receiving excessive loads. An ESAL value of 12790.07079 vehicles/day/2 directions was obtained from the calculation of vehicle traffic factors. Apart from that, the Truck Factor value is 2.74> 1, indicating that the Kimbim-Pyramid line is experiencing excessive load.